2013
DOI: 10.1186/1756-3305-6-299
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic filariasis in Luangwa District, South-East Zambia

Abstract: BackgroundPast case reports and recent data from LF mapping surveys indicate that LF occurs in Zambia, but no studies have been carried out to document its epidemiology and health implications. The present study assessed infection, disease, transmission and human perception aspects of LF in an endemic area of Luangwa District, South-East Zambia, as a background for planning and implementation of control.MethodsTwo neighbouring rural communities were registered and a questionnaire survey undertaken. Clinical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…It is a geochemical disease mainly characterized by lymphedema which is a condition of localized fluid retention resulting from a compromised lymphatic system [ 11 , 12 ]. The main clinical feature of podoconiosis, oedema of the foot and lower leg, is similar to that observed in filarial infection due to Wuchereria bancrofti [ 13 , 14 ]. In both diseases, lymphoedema progresses to elephantiasis.…”
Section: Introductionsupporting
confidence: 59%
“…It is a geochemical disease mainly characterized by lymphedema which is a condition of localized fluid retention resulting from a compromised lymphatic system [ 11 , 12 ]. The main clinical feature of podoconiosis, oedema of the foot and lower leg, is similar to that observed in filarial infection due to Wuchereria bancrofti [ 13 , 14 ]. In both diseases, lymphoedema progresses to elephantiasis.…”
Section: Introductionsupporting
confidence: 59%
“…Interestingly, our survey revealed that most of the respondents were aware of several ways used to control mosquito breeding, demonstrating some understanding of vector control strategies, although this knowledge was not necessarily translated to be part of an effective eradication program. While our results are in agreement with a previous study [ 20 , 27 ], a number of previous studies demonstrated that the majority of their subjects did not know the importance of minimizing mosquito contact in preventing infection [ 13 , 16 , 23 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…funestus and An. gambiae with LF transmission, however, transmission was not directly confirmed ( Shawa et al, 2013 ). Overall LF prevalence was found to be low (8.6%) and indicated a marked decline from prevalence measured in 2003 (33.3%) ( Mwase et al, 2014 ), which the authors attribute to the concurrent scale up of vector control in the area.…”
Section: Introductionmentioning
confidence: 99%